2008
DOI: 10.1097/fpc.0b013e3282f2f121
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in cytochrome P450 oxidoreductase influence microsomal P450-catalyzed drug metabolism

Abstract: Polymorphisms in the POR gene can affect POR and P450-catalyzed drug oxidation. These results suggest that POR has the potential to serve as a predictive biomarker for pharmacogenomic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 49 publications
4
63
3
Order By: Relevance
“…POR is the only electron donor for all microsomal P450s, and alteration in POR activity can affect P450-catalyzed drug oxidation (Hart et al, 2008). Our previous study revealed that the ontogenic mRNA expression of all P450s in the mouse liver and a large number of P450 genes had increased expression after birth (Peng et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…POR is the only electron donor for all microsomal P450s, and alteration in POR activity can affect P450-catalyzed drug oxidation (Hart et al, 2008). Our previous study revealed that the ontogenic mRNA expression of all P450s in the mouse liver and a large number of P450 genes had increased expression after birth (Peng et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…2. Two POR SNPs known to be associated with POR functional consequences: POR A503V (rs1057868) (causes ϳ30% decrease in POR activity) and POR rs41301472 (within intron 12, GϾA change, correlated with decreased POR activity in liver microsomes) (Hart et al, 2008 assembly, dbSNP b126), using the Annotate tag SNP Picker (Tagger Pairwise, R 2 cutoff: 0.8, MAF cutoff: 0.05): rs10280802, rs28737229, rs1057870, rs17148944, rs2868177, and rs17685 (http://www.hapmap.org/). 4.…”
Section: Methodsmentioning
confidence: 99%
“…Interindividual variations in POR activity (at least 4-to 5-fold differences) have been found in human liver microsomes (Kaminsky et al, 1984;Hart et al, 2008). The notion that variations in POR expression or activity influence the rates of P450-mediated drug metabolism in patients is supported by several lines of data, including the impact of Por gene knockout on drug clearance in mouse models (Gu et al, 2003;Henderson et al, 2003;Zhang et al, 2009), positive correlations between POR activity and P450-mediated drug metabolism activities in human liver microsomes (Kaminsky et al, 1984;Hart et al, 2008), and the impact of many POR single nucleotide polymorphisms (SNPs) on P450 activities toward drugs and other xenobiotics in reconstituted enzyme systems Flück et al, 2010;Marohnic et al, 2010;Nicolo et al, 2010;Sandee et al, 2010;Miller et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations